An Aspect-Oriented Approach for Supporting Autonomic Reconfiguration of Software Architectures - Costa-Soria, C.; Pérez, J.; Carsí, J.Á. (Informatica)
An Aspect-Oriented Approach for Supporting Autonomic Reconfiguration of Software Architectures